2021
DOI: 10.1101/2021.02.13.431041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic evidence that governmentally producedCannabis sativapoorly represents genetic variation available in state markets

Abstract: The National Institute on Drug Abuse (NIDA) is the sole producer of Cannabis for research purposes in the United States, including medical investigation. Previous research established that cannabinoid profiles in the NIDA varieties lacked diversity and potency relative to the Cannabis produced commercially. Additionally, microsatellite marker analyses have established that the NIDA varieties are genetically divergent form varieties produced in the private legal market. Here, we analyzed the genome of multiple … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Notably, most micropropagation protocols published in the United States are developed with Cannabis supplied by the University of Mississippi, who is funded through the National Institute on Drug Abuse (NIDA) as the sole licensed facility to supply Cannabis for research purposes in the United States [14,15]. There is mounting evidence that NIDA supplied Cannabis may not be representative of the broader population of Cannabis which can be obtained from commercial producers [14][15][16], and given this apparent discrepancy it is unknown if methods developed using NIDA supplied Cannabis will work effectively for commercially relevant genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, most micropropagation protocols published in the United States are developed with Cannabis supplied by the University of Mississippi, who is funded through the National Institute on Drug Abuse (NIDA) as the sole licensed facility to supply Cannabis for research purposes in the United States [14,15]. There is mounting evidence that NIDA supplied Cannabis may not be representative of the broader population of Cannabis which can be obtained from commercial producers [14][15][16], and given this apparent discrepancy it is unknown if methods developed using NIDA supplied Cannabis will work effectively for commercially relevant genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a long history of breeding for different purposes, drug-type C. sativa plants form genetically distinct clusters from fiber and grain types ( van Bakel et al, 2011 ; Sawler et al, 2015 ; Lynch et al, 2016 ; Vergara et al, 2021 ). Prior studies usually focused on marijuana, but sometimes included high CBD/low THC varieties as well.…”
Section: Introductionmentioning
confidence: 99%
“…Although Cannabis genetics has been developing quickly, the major focus is usually on marijuana-type C. sativa , with CBD-type hemp often much less represented (e.g., Lynch et al, 2016 ; Vergara et al, 2021 ). To date, there have been no studies that focus on the consistency of high-CBD hemp from the point of view of a commercial grower.…”
Section: Introductionmentioning
confidence: 99%
“…The genes giving rise to the cannabinoid synthases responsible for producing the major cannabinoid acids are highly similar (Vergara et al 2019;van Velzen and Schranz 2020;Vergara et al 2021b). Copy number variation (Vergara et al 2019;Vergara et al 2021b) or allelic variation (Onofri et al 2015) in the genes encoding these enzymes may explain the observed variation in cannabinoid ratios. Interesting areas of future study will be to correlate chemotype and genotype directly and determine why other minor cannabinoids have such low abundance in commercial Cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…These likely arise from distinct genotypes. The genes giving rise to the cannabinoid synthases responsible for producing the major cannabinoid acids are highly similar (Vergara et al 2019;van Velzen and Schranz 2020;Vergara et al 2021b). Copy number variation (Vergara et al 2019;Vergara et al 2021b) or allelic variation (Onofri et al 2015) in the genes encoding these enzymes may explain the observed variation in cannabinoid ratios.…”
Section: Discussionmentioning
confidence: 99%